2008
DOI: 10.1097/01.hp.0000281177.42452.8f
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Radon in Kuwait

Abstract: Indoor radon measurements were carried out in 300 dwellings in Kuwait using duplicate sets of charcoal detectors. Measurements were made at three different locations in the dwellings: living rooms, bedrooms, and basements. The results show that the radon concentration in the dwellings of Kuwait was found to vary in the range of 4.0-241.8 Bq m(-3) with a mean value of 32.8 Bq m(-3), and most values are confined within the range of 10-50 Bq m(-3) for all locations with few cases above the value of 100 Bq m(-3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…It has been the subject of numerous studies and investigations in the word. [1][2][3][4][5][6] The human environment is one in which ionizing radiations are present at all time and at all places on the earth from the deepest cellars to the highest mountains and on into space. Radon and its decay products are present wherever radium and thorium exist in the earth or in any planetary material.…”
Section: Introductionmentioning
confidence: 99%
“…It has been the subject of numerous studies and investigations in the word. [1][2][3][4][5][6] The human environment is one in which ionizing radiations are present at all time and at all places on the earth from the deepest cellars to the highest mountains and on into space. Radon and its decay products are present wherever radium and thorium exist in the earth or in any planetary material.…”
Section: Introductionmentioning
confidence: 99%
“…The comments made by Cigna and Badino about the statement "Since radon is a heavy gas (atomic number 86), it accumulates at the lower levels of dwellings" (page 52 of our paper; Al-Azmi et al 2008), are also well taken. However, in the context of our paper, we did not attribute radon accumulation in basements to its sedimentation in air, but rather to poor ventilation.…”
Section: Reply To Cigna and Badinomentioning
confidence: 62%
“…The paper by Al-Azmi et al (2008) is interesting because it supplies data for a region with a climate quite different from Europe or North America. Notwithstanding the use of detectors with an exposure time of 2 days, the result of the whole research gives a general view of the distribution of radon concentration in Kuwait homes.…”
Section: Dear Editorsmentioning
confidence: 99%
“…However, some high values were obtained during these screenings, which were mainly due either to the inhabitants' habits or to the design and structure of the measured place. The seasonal effect on the radon concentrations in houses was investigated in Kuwait (Al-Azmi et al, 2008) and Libya and no significant effects were found. It is believed that the moderate climate in both countries, which allows natural ventilation of the houses, contributes to the non-significant effect of seasons on the indoor levels of radon in the area.…”
Section: Discussionmentioning
confidence: 99%